An update on the risk factors for and management of obstetric haemorrhage. (August 2017) - Sebghati, Mercede; Chandraharan, Edwin
Obstetric haemorrhage is associated with increased risk of serious maternal morbidity and mortality. Postpartum haemorrhage is the commonest form of obstetric haemorrhage, and worldwide, a woman dies due to massive postpartum haemorrhage approximately every 4 min. In addition, many experience serious morbidity such as multi-organ failure, complications of multiple blood transfusions, peripartum hysterectomy and unintended damage to pelvic organs, loss of fertility and psychological sequelae, including posttraumatic stress disorders. Anticipation of massive postpartum haemorrhage, prompt recognition of the cause and institution of timely and appropriate measures to control bleeding and replacement of the lost blood volume and restoration of oxygen carrying capacity (i.e. haemoglobin) and correction of the 'washout phenomenon' leading to coagulopathy will help save lives. Obstetric shock index may help in avoidance of underestimation of blood loss and the use of tranexamic acid, oxytocics and timely peripartum hysterectomy, if appropriate, will help save lives. Triple P procedure has been recently developed as the conservative surgical alternative for women with abnormal invasion of the placenta and has been shown to significantly reduce the blood loss and to reduce inpatient stay.